2010
DOI: 10.1007/s10765-010-0740-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Cobalt-Based Catalyst for Fischer–Tropsch Synthesis

Abstract: In this study, the thermal conductivity of cobalt-based catalyst specimens in the temperature range from 160 • C to 255 • C are measured via a steady-state apparatus. The apparatus and procedures are applied to several specimens of cobalt-based catalyst powder compacts. Specimens with different degrees of porosity are produced by pressing cobalt-based catalyst powder with a particle size of (80 to 360) mesh. The thermal conductivity of cobalt-based catalyst powder compacts is investigated as functions of tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The effective thermal conductivity of the bed is calculated from the volume-averaging of the bulk fluid (k f ) and solidphase (k p ) thermal conductivities. The latter is obtained from a volume-averaging of dense inert packing and porous catalyst thermal conductivities, with the former assumed as copper to represent MFECC fibers with k Cu 5380 W=m K (adopted from Yaws critical database 49 ), while the effective thermal conductivity is calculated as follows 50 @T @r 50 @ r50; @T @r 5h T c 2T ð Þ@ r5r bed ; T5T o @ z5z 3 ; @T @z 50 @ z50 (18) In all case scenarios considered in this study, the coolant temperature was maintained equal to the inlet gas flow temperature, and the wall boundary heat-transfer coefficient (h) was evaluated as k w 512 W=m K, assuming a stainless steel of wall thickness 1:5310 24 m.…”
Section: Heat Transport Expressionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The effective thermal conductivity of the bed is calculated from the volume-averaging of the bulk fluid (k f ) and solidphase (k p ) thermal conductivities. The latter is obtained from a volume-averaging of dense inert packing and porous catalyst thermal conductivities, with the former assumed as copper to represent MFECC fibers with k Cu 5380 W=m K (adopted from Yaws critical database 49 ), while the effective thermal conductivity is calculated as follows 50 @T @r 50 @ r50; @T @r 5h T c 2T ð Þ@ r5r bed ; T5T o @ z5z 3 ; @T @z 50 @ z50 (18) In all case scenarios considered in this study, the coolant temperature was maintained equal to the inlet gas flow temperature, and the wall boundary heat-transfer coefficient (h) was evaluated as k w 512 W=m K, assuming a stainless steel of wall thickness 1:5310 24 m.…”
Section: Heat Transport Expressionsmentioning
confidence: 99%
“…The pellet solid‐phase thermal conductivity was determined via previously developed correlation fitted to data provided in Ref. for cobalt‐based FTS catalysts λnormalp=0.8652+0.00108|T273.15 …”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…A model with a linear variation of λ er in the vicinity of the wall is proposed to the description of the radial heat transfer in the packed bed. Wu et al [25] investigated the thermal conductivity of catalyst powder compacts and found that the thermal conductivity of the catalyst specimens increases linearly with temperature and density and practically independent of the particle size of the powder in an atmosphere of air, while the porosity dependence of the thermal conductivity is inverse to that of density. Because of the critical importance of heat exchange, mathematical models should be able to represent satisfactorily the relatively complex heat transfer mechanism inside the bed.…”
Section: Introductionmentioning
confidence: 99%